2021
DOI: 10.1161/circulationaha.121.053782
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Using Dual Versus Monotherapy Antiplatelet Agents in Secondary Stroke Prevention: Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials

Abstract: Background: Dual antiplatelet treatment (DAPT) with aspirin plus clopidogrel for a limited time is recommended after minor non-cardioembolic stroke. Methods: We performed a meta-analysis of all major studies that compared the efficacy and safety of DAPT versus monotherapy for secondary prevention of recurrent stroke or transient ischemic attack (TIA). The primary outcomes were stroke and the composite of stroke, TIA, acute coronary syndrome and death of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Cochrane systematic review, pooled data analysis and meta-analysis of RCTs demonstrated that DAPT with aspirin and clopidogrel or ticagrelor for 21–30 days is more effective than SAPT for secondary stroke prevention when initiated early after the onset of minor stroke or high-risk TIA 3 6–9. However, when initiated later and used longer than 90 days, DAPT increases the risk of bleeding without reduction of stroke recurrence than SAPT 7–9…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cochrane systematic review, pooled data analysis and meta-analysis of RCTs demonstrated that DAPT with aspirin and clopidogrel or ticagrelor for 21–30 days is more effective than SAPT for secondary stroke prevention when initiated early after the onset of minor stroke or high-risk TIA 3 6–9. However, when initiated later and used longer than 90 days, DAPT increases the risk of bleeding without reduction of stroke recurrence than SAPT 7–9…”
Section: Resultsmentioning
confidence: 99%
“…The current evidence-based recommendations on antiplatelet therapy for secondary stroke prevention are summarised in table 3 3–10…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…209 Clopidogrel added to aspirin for patients with transient ischemic attack (TIA) or ischemic stroke appears to significantly decrease the risk of ischemic stroke recurrence, but again there is an elevated risk of bleeding vs aspirin alone. [210][211][212] Interestingly, the data in support of clopidogrel monotherapy over other antiplatelet agents is limited by the small numbers of studies that directly compare clopidogrel as single antiplatelet therapy. A meta-analysis of 5 studies indicated that clopidogrel monotherapy for secondary stroke prevention may reduce risks of major adverse CV or cerebrovascular events, recurrent stroke, and bleeding events compared with aspirin.…”
Section: Strokementioning
confidence: 99%